The effect of vascular endothelial growth factor VEGF-A gene polymorphisms and intravitreal anti-VEGF treatment outcomes in patients with exudative age-related macular degeneration - Kubicka-Trząska, Agnieszka; Karska-Basta, Izabella; Dziedzina, Sylwia; Sanak, Marek; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Aim : To analyse the correlation between the rs2146323 and rs699947 polymorphisms of VEGF-A gene and the risk of age-related macular degeneration and response to anti-VEGF therapy in affected patients. Material and methods : 106 patients with exudative age-related macular degeneration treated with intravitreal ranibizumab or bevacizumab were enrolled. Treatment response was assessed at 4-week intervals for 6 months and was based on the best corrected visual acuity and central retinal thickness compared to the baseline status. The control group included 60 subjects without age-related macular degeneration. Genetic testing (TaqMan Applied Biosystems) was performed in all cases. Results : There was no correlation between the rs2146323 polymorphism of VEGF-A gene and age-related macular degeneration; yet, there was a correlation between this polymorphism and anti-VEGF treatment outcomes. Patients with CC genotype of rs2146323 VEGF-A polymorphism demonstrated significantly better treatment response. At the end of a follow-up, age-related macular degeneration patients with positive CC genotype of rs2146323 VEGF-A gene polymorphism had final better best corrected visual acuity and showed significant central retinal thickness reduction as compared to individuals negative for this genotype (OR = 2.65, 95% CI (1.17–5.99); p = 0.0171). Among the 25.47% of “non-responders”, genotype CC of rs2146323 VEGF-A was present in 28.85% of cases, while genotype AC was detected in 61.54% of cases (p = 0.0128). There was no correlation between rs699947 VEGF-A polymorphism and either age-related macular degeneration or response to anti-VEGF treatment. Conclusions : The study showed that rs2146323 and rs699947 VEGF-A polymorphisms are not associated with increased risk of age-related macular degeneration. However, the rs2146323 VEGF-A polymorphism modulated the response to anti-VEGF therapy. Genotype CC of rs2146323 was associated with an improved response to anti-VEGF treatment, while patients with genotype AC of rs2146323 showed worse functional and anatomical response to anti-VEGF agents.